Dos sabores fortes aos suaves: os limites da modernização à francesa nos livros de cozinha da corte portuguesa, 1680-1780 - Viana Junior, Fernando Santa Clara (2015)
We present the trajectory of modern European cuisine, born in France from the late sixteenth century, toward the other national borders, focusing on Portugal. This movement encompassed from the culinary practices, the use of ingredients, techniques and even the food rituals that have been consolidated as distinctions of time. To analyze this process in the Portuguese case we start from the first two cookbooks published in Portugal: Kitchen Art (1680) written by Dominic Rodrigues and Modern Cook or New Kitchen Art (1780) written by Lucas Rigaud. These are the main portuguese works dedicated to the kitchen in modernity and of great importance to the historical context in this Kingdom when it was published. It is important for us, therefore, from the analysis of these sources, see what the limits of French influence, in which ways it indeed proved and what features found associated with survival of attributes considered still medieval therefore removed this modernization. In this way, we seek to finally map sensibilities, tastes and cultural meanings circulating in Portugal between 1680-1780, which allowed evaluating roughly the proposition of changes in eating patterns that marked the Old World in this context, with its innovations and stays